Tingkat Kesiapan Dengan Kecemasan Dalam Menghadapi Persalinan Pada Ibu Bersalin: Level of Readiness and Anxiety in Facing Childbirth in Maternal Mothers - Frastika, Ika (Jurnal Abdi Keperawatan dan Kedokteran, 2022)
The process of labor generally mothers feel high anxiety. Readiness of labor is a support system for pregnant women to help and motivate pregnant women to improve the quality of their health and psychological conditions that pregnant women feel loved and cared for during pregnancy so as to reduce anxiety response. Objective To find out whether there is a relationship between the Level of Readiness and Anxiety in Facing Labor at Maternity at the Galang Health Center Tolitoli District, Central Sulawesi. The design used in the study was Cross Sectional. The population is all maternity mothers. The sample size is 30 respondents using Accidental sampling technique. The independent variable of the study is the Readiness Level. The dependent variable is anxiety. Data was collected using a questionnaire, then the data were analyzed using the Spearment RHO test with a significance level of α ≤ 0.05. The results of the study showed that most respondents were not prepared for delivery as many as 16 respondents (53.3%), mild anxiety as many as 15 respondents (50%). The results showed that p = 0,000 where H1 was accepted and H0 was rejected, which means that there was a relationship between the level of readiness and anxiety in facing childbirth at maternity at Galang Puskesmas Tolitoli, Central Sulawesi. There is a correlation between the Level of Readiness and Anxiety in Facing Labor at Maternity at theGalang Health Center Tolitoli District, Central Sulawesi. Good mother's readiness will reduce the risk ofanxiety in childbirth.